(14) The Effect of Using Technology on Gender Wage Gap in the Egyptian Labor Market أثر استخدام التكنولوجيا على فجوة الأجر وفقاً للنوع الاجتماعي في سوق العمل في مصر - Adel Riad, Marina (معهد التخطيط القومى, 2025)
This study presents a novel approach to analyzing gender wage disparities in the Egyptian labor market, focusing on the role of technological advancements amid the country's ongoing economic reforms and digital transformation. Despite gains in female education and labor force participation, the gender wage gap persists. Unlike previous research, this paper investigates the impact of skill-biased technological change on wage dynamics, offering new insights for policymakers. Drawing on data from the 2023 Egypt Labor Market Panel Survey, the study employs robust econometric methods—including Ordinary Least Squares (OLS), Instrumental Variable Two-Stage Least Squares (IV-2SLS), and the Neuman-Oaxaca decomposition—to estimate gender wage differentials across varying levels of technological exposure. Workers are categorized into three groups: technology professionals, technology users, and non-users. Key findings reveal that while technology professionals experience the narrowest gender wage gap, significant disparities remain, with 91.4% of the gap unexplained. In contrast, technology users and non-users face larger and more persistent wage gaps, reflecting structural barriers and occupational segregation. Notably, higher technological proficiency is associated with reduced wage disparities, underscoring the importance of digital skills in promoting gender equity in the labor market. However, women’s rising education levels also correspond with lower tolerance for substandard working conditions. Based on these results, the study recommends targeted policy interventions, including: